Analysis of the Open Data Landscape in Mexico - Alvarado Uribe, Joanna (2023)
The concept of open data originated from the idea of making government data available to anyone. In 2013, the Mexican government launched the National Digital Strategy to encourage the adoption and development of information by implementing five key enablers, including an open data portal to make government data more accessible to citizens. In 2014, the beta version of the datos.gob.mx portal was launched. Due to the significant potential of data to generate benefits, it has been referred to as the new gold. However, open data also presents some challenges, such as lack of interoperability and reproducibility and the resources needed to provide and maintain open data available to all. Therefore, based on the transversal agenda REMERI-ANUIES-EduTraDi focused on Open Science Ecosystems, the objectives of this research are to identify and analyze institutional repositories promoting Open Data in Mexico in order to document their characteristics and determine possible areas for improvement in such initiatives. This investigation allowed the identification of ten repositories promoting open data in Mexico and the integration of 16 characteristics that helped to describe and analyze the open data landscape, showing that the different open data management efforts carried out by Mexican institutions are mostly consolidated.